A Concordance Study between Polymerase Chain Reaction Assay and Conventional Culture-based Methods for Detection of Fusobacterium necrophorum (Indian Journal of Forensic Medicine & Toxicology, 2020)
Foot rot duo to Fusobacterium necrophorum is an important clinical economic disease in ovine, in order to inform identification and antibiotics selection, Conventional culture-based method and Polymerase chain reaction assays had been proposed to provide a good inter-rater reliability between these techniques, this study was aimed to differentiate the accuracy of conventional culture-based method and PCR technique for identification of Fusobacterium necrophorum in an ovine foot rot. Method: The current study was conducted on three farms of Kerbala governorate (AL-husseinyia, Al-Hurr and Ain Al-tmor cities) during the period from October 2017 to April 2018, pathological swab samples of the interdigital region of affected (n= 40) sheep and (n=40) goat were enrolled in this study, after the collection of swabs, the samples were divided into two partitions, each swab of the first partition was immediately collected into lighten tube containing 5 mL of thioglycollate broth enriched with 0.5% ground sheep and was transmitted to the laboratory for conventional culture-based method and the another partition of swabs was sealed with other cooled tubes containing 5 mL of thioglycollate broth enriched with 0.5% ground sheep for the laboratory of molecular investigations. Results: Fusobacterium necrophorum was identified in the pathological samples by the two following depended assays: and (46) swabs were positive by conventional culture-based method and (44) swabs were positive with PCR assay, Cohen’s kappa coefficient revealed P value for conventional culture-based methods vs. PCR assay of 0.056 and the current study was demonstrated a highly identification rates of Fusobacterium necrophorum in conventional culture-based methods rather than PCR assay. Conclusions: Current study documented conventional culture-based method and PCR assays were facilitate the identification of Fusobacterium necrophorum in case of presumed ovine foot rot, it also concluded that molecular assays should be depended in confirmatory detection of F. necrophorum in affected animals.
Keywords: Foot Rot, Fusobacterium necroforum, PCR, Sheep, goat